2017
DOI: 10.22610/jebs.v9i1(j).1555
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Barriers that are Confronted by Entrepreneurs Living with Physical Disabilities: A Thematic Analysis

Abstract: Living with a physical disability can interfere with an individual’s ability to participate actively in economic and social life. It is imperative to comprehensively understand the entrepreneurial barriers hindering the development of entrepreneurs living with physical disabilities. In spite of the increasing research on entrepreneurship, there seems to be a paucity of studies that have investigated the entrepreneurial barriers that are faced by entrepreneurs living with physical disabilities in South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The discussion in this research paper is presented in line with the themes that arose from the focus group and interview transcripts. Thematic analysis is defined as a meticulous process of identifying, analysing and reporting themes that emerge from a qualitative study (Maziriri et al, 2017). Thematic analysis is regarded as the "foundational method for qualitative analysis" and was the chosen to formally commerce the analytical process given its suitability to the exploratory nature of the research (Apolloni, 2010. p. 88).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discussion in this research paper is presented in line with the themes that arose from the focus group and interview transcripts. Thematic analysis is defined as a meticulous process of identifying, analysing and reporting themes that emerge from a qualitative study (Maziriri et al, 2017). Thematic analysis is regarded as the "foundational method for qualitative analysis" and was the chosen to formally commerce the analytical process given its suitability to the exploratory nature of the research (Apolloni, 2010. p. 88).…”
Section: Resultsmentioning
confidence: 99%
“…Thematic analysis is regarded as the "foundational method for qualitative analysis" and was the chosen to formally commerce the analytical process given its suitability to the exploratory nature of the research (Apolloni, 2010. p. 88). The major advantage of thematic analysis is that it is a logical process that allows the researcher to scrutinize interview transcripts comprehensively and glean all possible themes (Maziriri et al, 2017;Muposhi, 2015. p. 168;Muposhi et al, 2015. p. 230). The following framework indicates the main themes identified in the data sources.…”
Section: Resultsmentioning
confidence: 99%
“…Singh and Singh (2016) report that positive attitude, motivation and perceived behavioral control are the qualifications of entrepreneurial inclination. Previous studies conducted globally, recognised entrepreneurship as a tool for driving a nation's economy (Chell et al, 2016;Gree & Thurnik, 2003;Iwu et al, 2016;Maziriri & Madinga, 2016;Maziriri et al, 2017). Sandhu et al (2011) outlined the barriers of entrepreneurship to be aversion to stress and hard work, aversion to risk, fear of failure, lack of social networking, lack of resources, and demographic and personal factors.…”
Section: Resultsmentioning
confidence: 99%
“…This information is relevant as this research is concerned with entrepreneurial inclination. Previous authors (such as Burger, Mahadea & Neil, 2004;Maziriri & Madinga, 2016;Maziriri, Madinga & Lose, 2017;Steenekamp, Van der Merwe & Athayde, 2011) have reported that South African population (the youth inclusive) does not suffer from a lack of creative spirit, but from a lack of business education and entrepreneurial skills that can empower them in an enabling environment. Iwu et al (2016) put forward that among other factors, the socioeconomic conditions and education system are the most critical factors influencing the development of entrepreneurship in the global economy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation